2010
DOI: 10.1089/jwh.2008.1334
|View full text |Cite
|
Sign up to set email alerts
|

Economic Risk Factors for HIV Infection Among Women in Rural Haiti: Implications for HIV Prevention Policies and Programs in Resource-Poor Settings

Abstract: Aims: The goals of this study were to (1) estimate the prevalence of HIV infection among women accessing services at a women's health center in rural Haiti and (2) to identify economic risk factors for HIV infection in this population. Methods: Women who accessed healthcare services at this center between June 1999 and December 2002 were recruited to participate. The analysis was based on data from a case-control study of sexually transmitted diseases (STDs) in rural Haiti. HIV prevalence in the study populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
5
0
5
Order By: Relevance
“…Thus, stigma is a challenge when treating and caring for persons with HIV infection. The fear associated with being stigmatized may cause individuals to avoid care and services (Cox, 2002;Fawzi et al, 2010;DeSantis, Thomas, & Sinnett, 1999;Arrivillaga et al, 2011;Do et al, 2010). This fear is also associated with the lack of protective behaviors such as adherence to ART (Fawzi et al, 2010;DeSantis et al, 1999;Arrivillaga et al, 2011;Do et al, 2010).…”
Section: Social Factors Associated With Art Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, stigma is a challenge when treating and caring for persons with HIV infection. The fear associated with being stigmatized may cause individuals to avoid care and services (Cox, 2002;Fawzi et al, 2010;DeSantis, Thomas, & Sinnett, 1999;Arrivillaga et al, 2011;Do et al, 2010). This fear is also associated with the lack of protective behaviors such as adherence to ART (Fawzi et al, 2010;DeSantis et al, 1999;Arrivillaga et al, 2011;Do et al, 2010).…”
Section: Social Factors Associated With Art Adherencementioning
confidence: 99%
“…Studies have found that stigma may be problematic especially among females (Fawzi et al, 2010;DeSantis, Thomas, & Sinnett, 1999;Arrivillaga et al, 2011;Do et al, 2010;Mills et al, 2006;Lillard & Panis, 1996;Smith & Waitzman, 1994;Bourne, 2009;Waldron, Hughes, & Brooks, 1996).…”
Section: Perceived Stigma and Adherence In Femalesmentioning
confidence: 99%
“…This proportion represents an increase from 46% in and 53% in 2007(UNAIDS, 2013aUNAIDS, 2008). Retrospective analyses have indicated that some of the most common risk factors associated with HIV infection among Haitian women living in Haiti include multiple lifetime sexual partners, lack of condom use within or outside of monogamous relationships, lack of education, and economic hardship (Logie, Daniel, Newman, & Loutfy, 2012;Rosenberg, Seavey, Jules, & Kershaw, 2011;Fawzi et al, 2010;Fawzi et al, 2003;Deschamps & Pape, 1996). While these risk factors appear to be the most common among Haitian women infected with HIV, other risk factors, such as childhood sexual abuse, may also contribute to the prevalence of HIV among this population.…”
Section: According To the Latest Joint United Nations Programme On Himentioning
confidence: 99%
“…Instead, many couples enter into an informal union called plasaj (Purcell, 2012;Fawzi, 2010;Boesten, 2009). In a plasaj, a woman enters into a long-term union with an unmarried man to support their children and family.…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation